Targeting microglial NAAA-regulated PEA signaling counters inflammatory damage and symptom progression of post-stroke anxiety - Tianyue Yin; Shuaijie Sun; Li Peng; Mengmeng Yang; Mengyu Li; Xinlu Yang; Fengyun Yuan; Hongrui Zhu; Sheng Wang (Cell Communication and Signaling)
Abstract Post-stroke anxiety (PSA) manifests as anxiety symptoms after stroke, with unclear mechanisms and limited treatment strategies. Endocannabinoids, reported to mitigate fear, anxiety, and stress, undergo dynamic alterations after stroke linked to prognosis intricately. However, endocannabinoid metabolism in ischemic microenvironment and their associations with post-stroke anxiety-like behavior remain largely uncovered. Our findings indicated that endocannabinoid metabolism was dysregulated after stroke, characterized by elevated N-palmitoylethanolamide (PEA) hydrolase N-acylethanolamine-acid amidase (NAAA) in activated microglia from ischemic area, accompanied by rapid PEA exhaustion. Microglial PEA metabolite exhaustion is directly associated with more severe pathological damage, anxiety symptoms and pain sensitivity. Naaa knockout or pharmacological supplementation to boost PEA pool content can effectively promote stroke recovery and alleviate anxiety-like behaviors. In addition, maintaining PEA pool content in ischemic area reduces overactivated microglia by confronting against mitochondria dysfunction and inflammasome cascade triggered IL-18 release and diffusion to contralateral hemisphere. Meanwhile, maintenance of microglial PEA pool content in ischemic-damaged lesion can preserve contralateral vCA1 synaptic integrity, enhancing anxiolytic pBLA-vCA1Calb1+ circuit activity by alleviating microglial phagocytosis-mediated synaptic loss. Thus, we conclude that microglial NAAA-regulated lipid signaling in the ischemic focus remodels contralateral anxiolytic circuit to participate in post-stroke anxiety progression. Blocking PEA signaling breakdown promotes stroke recovery and mitigates anxiety-like symptoms. Graphical Abstract Microglial NAAA-regulated lipid signaling involves with post-stroke anxiety.